2016
DOI: 10.4238/gmr15048822
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL18-607C/A and -137G/C polymorphisms and susceptibility to non-small cell lung cancer in a Chinese population

Abstract: Lung cancer is one of the main causes of cancer-related mortality in males and females worldwide. A pleiotropic effect has been observed in the interleukin 18 gene (IL18); its effects include the activation of natural killer cell cytotoxicity and the promotion of the Th1 immune response through the alteration of the expression of interferon-γ and TNF-α in humans. IL18 is therefore involved in the elimination of tumor cells in the human body. We recruited 357 patients with non-small cell lung cancer (NSCLC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…(5,28,29) SNPs of the following genes are reported to be associated with the burden of pain and with the development of depression and fatigue in patients with lung malignancy NOS3 (1474 T>A, rs1800783), IL1B (allele 31C, rs1143627), TNFR2 (Met196Arg, rs1061622), PTGS2 (837T>C, rs5275), IL10RB (Lys47Glu, rs2834167) (30) against the background of existing non-genetic factors (the patient's sex, the stage of cancer). (31,32) SNP 174G>C (rs1800795) of the promoter of the IL-6 gene is associated with alterations in the serum level of the cognominal cytokine IL-6. Homozygous carriers of the GG genotype have a higher level of IL-6 expression in comparison with homozygous carriers of the CC genotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,28,29) SNPs of the following genes are reported to be associated with the burden of pain and with the development of depression and fatigue in patients with lung malignancy NOS3 (1474 T>A, rs1800783), IL1B (allele 31C, rs1143627), TNFR2 (Met196Arg, rs1061622), PTGS2 (837T>C, rs5275), IL10RB (Lys47Glu, rs2834167) (30) against the background of existing non-genetic factors (the patient's sex, the stage of cancer). (31,32) SNP 174G>C (rs1800795) of the promoter of the IL-6 gene is associated with alterations in the serum level of the cognominal cytokine IL-6. Homozygous carriers of the GG genotype have a higher level of IL-6 expression in comparison with homozygous carriers of the CC genotype.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of non-small cell lung cancer in the Chinese population (32) The risk of pancreatic cancer (50) IL4 IL-4R 590 C>T (rs2243250) rs2243228 rs2227284 rs2070874…”
Section: C>amentioning
confidence: 99%
“…IL-18 is involved in the carcinogenesis of multiple cancers. Accumulating evidence indicated that the IL-18 promoter genotype was correlated with the risk of PC, nasopharyngeal carcinoma (NPC), HCC and NSCLC [182,183,184,185]. Moreover, genetic polymorphisms of IL-18 were linked with the prognosis and survival of patients with acute myeloid leukemia (AML) [186].…”
Section: The Emerging Role Of Inflammasome-dependent Cytokines In mentioning
confidence: 99%
“…С тяжелым бременем развития боли, депрес-сии и усталости у пациентов с ЗНО легких свя-заны ОНП следующих генов: ENOS (1474 T>A, rs1800783), IL1BT (аллель 31C, rs1143627), TNFR2 (Met196Arg, rs1061622), PTGS2 (837T>C, rs5275), IL10RB (Lys47Glu, rs2834167) [30] на фоне имею-щихся не генетических факторов (пол пациента, стадия ЗНО) [31,32].…”
Section: гены цитокиновunclassified